Successful Renal Transplantation between Identical Twins with Very Brief Immunosuppression - Idris Yakubu; Abdolreza Haririan; Stephen Bartlett; Tracy Sparkes (Case Reports in Transplantation)
Renal transplantation between monozygous identical twins provides an opportunity to utilize minimal immunosuppression to maintain stable allograft function, thereby alleviating the toxicities of immunosuppressive therapy. Despite monozygosity, there is a possibility of discordant protein presentation in identical twins that could trigger alloimmune response and lead to graft injury. Therefore, the optimal immunosuppression regimen in this patient population is unknown, and the safety of immunosuppression withdrawal remains controversial. Herein, we describe two patients who underwent successful renal transplantation from monozygotic identical twin donors. Monozygosity was determined using short tandem repeat (STR) analysis. All immunosuppression was successfully discontinued at 2 days and 3 weeks, respectively, after transplantation. Both patients are alive with functioning renal grafts at 1 year and 5 years after transplant, respectively. These two cases suggest that immunosuppression can be withdrawn safely and rapidly in select monozygous identical twin renal transplant recipients.